THE RELATIONSHIP BETWEEN SOFT DRINK CONSUMPTION AND CHRONIC KIDNEY DISEASE IN MUHAMMADIYAH PALEMBANG HOSPITAL - Permana, Adhi; Purwoko, Mitayani; Azzahra, Rashieka Adawiya (Faculty of Medicine, 2024)
Chronic kidney disease (CKD) has become one of the leading causes of death worldwide. It is one of several non-communicable diseases that have seen an associated increase in mortality over the past two decades. The causes of decreased kidney function are due to several factors, including a history of hypertension, cardiovascular history, family history of CKD, history of drinking preserved beverages, colored beverages, and other chemicals, and older age groups. Consuming soft drinks is associated with diabetes, hypertension, and kidney stones as risk factors for chronic kidney disease. This study aims to analyze the relationship between the frequency of soft drinks and chronic kidney disease at the Muhammadiyah Palembang Hospital. The sample of this study was 47 cases and 47 controls with an analytic observational research design with a case-control approach. This study used questionnaires and medical record data at the Palembang Muhammadiyah Hospital. Sampling used a consecutive sampling technique. The results showed that 61.7% of CKD patients and 55.3% of control subjects consumed soft drinks. The types of soft drinks consumed by CKD patients and control subjects were soft drinks with added sweeteners (100.0%). The results of the Pearson Chi-square test showed a value of p=0.644 (p>0.05). This study concluded that there is no relationship between the frequency of soft drinks and chronic kidney disease.